The role of public-private partnerships in cleaner production programs: enhancing environmental performance in Malaysia’s manufacturing sector - Mohd Nasir Nawawi; Rahmah Abdullah; Suriyani Muhamad; Muhammad Najit Sukemi; Nizam Ahmat (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to analyze the factors influencing the quality of Public-Private Partnerships (PPP) and their impact on environmental performance among factories participating in the Cleaner Production program. We employ the theory of cooperation to determine how seven attributes affect the quality of PPP and environmental performance within 148 manufacturing firms involved in the Cleaner Production (CP) program organized by the Department of Environment Malaysia (DOE). The study findings revealed that partnership quality in the Cleaner Production program has been positively and significantly influenced by information sharing, communication quality, top management support and skills. In addition, the quality of the partnership has a significant positive impact on the reduction of raw material, energy savings and waste management costs. Recently, much research has focused on PPPs on mega-project, especially economics infrastructure and social infrastructure. This study adapts the theoretical framework of PPP in a pollution reduction project that has received little attention. PPPs enhance partnership quality by offering firms shared resources, incentives, and expertise, helping achieve environmental goals. These initiatives promote voluntary actions beyond compliance, like reducing raw material use, boosting energy efficiency, and cutting waste management costs, fostering proactive efforts for sustainable practices.